Cognitive functioning and psychosomatic syndromes in a subjective tinnitus sample - Gasparre, Daphne; Pepe, Ilaria; Laera, Domenico; Abbatantuono, Chiara; De Caro, Maria Fara; Taurino, Alessandro; D’Erasmo, Daniele; Fanizzi, Piero; Antonucci, Linda A.; Pantaleo, Alessandra; Cavallaro, Giada; Pontillo, Vito; et al. (Frontiers in Psychology, 2023)
Tinnitus is the perception of a sound in the absence of any corresponding external sound source. Current research suggests a relationship among emotional, cognitive, and psychosomatic symptoms and the occurrence or maintenance of chronic tinnitus. This study aimed to detect the prevalence and role of psychosomatic conditions, as defined by the Diagnostic Criteria for Psychosomatic Research (DCPR), and cognitive functioning in a group of patients with tinnitus. Sixty-two patients with subjective tinnitus and 62 non-tinnitus controls were recruited from the Otorhinolaryngology Unit of the University of Bari. Pure-tone audiometry was performed in all tinnitus subjects, and sound level tolerance was evaluated. Additionally, tinnitus handicap (Tinnitus Handicap Inventory [THI]), psychopathological symptoms (Symptom Checklist-90, Revised [SCL-90-R]), anxiety (State-Trait Anxiety Inventory [STAI-Y1/2]), depression (Beck Depression Inventory [BDI]), cognitive impairment (Mini-Mental State Examination [MMSE]), executive functions (Frontal Assessment Battery [FAB]), and psychosomatic syndromes (DCPR) were evaluated. Parametric and non-parametric tests were used to detect cognitive and symptomatological differences between patients and controls. The predictivity of these factors for tinnitus severity was studied using multiple regression (Backward Elimination). All tests were considered significant at p<0.05 (family wise error corrected for each comparison). 69.4% tinnitus patients met multiple DCPR criteria, compared to 32.3% of controls. Tinnitus patients exhibited elevated rates of illness denial (ꭓ2= 9.02; p<0.009), demoralization (ꭓ2= 8.05; p< 0.018), somatization (ꭓ2= 4.92; p< 0.063) and functional symptoms (ꭓ2= 5.21; p< 0.06) scoring significantly higher on the BDI, STAI-Y1 and STAI-Y2, and SCL-90-R compared to controls. Patients with tinnitus showed lower MMSE scores, compared to controls (t= -2.282; p< 0.001). No association between tinnitus severity and global cognitive impairment emerged. Conversely, executive function deficits were associated to tinnitus severity. Among the cognitive and psychological factors, only trait anxiety, one or more psychosomatic syndromes, and somatization clusters were strongly correlated with tinnitus severity. Our findings suggest a relationship between tinnitus severity, psychological, psychosomatic symptoms, and frontal impairment. Additionally, the influence of tinnitus on cognitive functions paves the way for integrated, multidisciplinary diagnostic and treatment options for patients. Although preliminary, our findings highlight the importance of early cognitive and psychological screening to improve patients' quality of life.